Plan do check action (PDCA) method: literature review and research issues - Isniah, Sarah; Hardi Purba, Humiras; Debora, Fransisca (Jurnal Sistem dan Manajemen Industri, 2020)
The development of the industry that is increasingly making businesses try to be competitive by increasing technical knowledge and improving systems both internally and externally. PDCA is a quality management system that is used as a continuous improveÂment tool that is widely used in the service and manufacturing sectors. PDCA activities consist of four steps namely Plan, Do, Check, and Action with repeated stages forming like a circle. PDCA is a continuous improvement tool that is widely used in the services and manufacturing sector. The cycle of PDCA begins with small to check possible effects on systems, but then eventually progresses to larger and more specific improvements. The results of the implementation PDCA method can be used to solve the problems of qualitative and quantitative data problems that have been widely applied in the service and manufacturing sectors for continuous improvement and as a work pattern in improving a process or system in an organization and increasing productivity. The method used in this research is the literature review research paper has been published in 2015-2020 that have consistently applied the PDCA cycle. The result of this literature review is to describe the relationship between thinking or gaps in theoretical and practical thinking about the application of the PDCA method and the successful implementation in the service and manufacturing sectors as a contribution to further research.